2013
DOI: 10.1038/bjc.2013.208
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse transcriptase inhibition stimulates cyclooxygenase 2 expression in cancer cells and synergizes with celecoxib to exert anti-cancer effects

Abstract: Background:Telomerase and telomerase reverse transcriptase (hTERT) confer cancer cells sustained proliferation and survival potentials. Targeting telomerase or hTERT is a novel anti-cancer strategy. However, telomerase/hTERT inhibition alone has minimal clinical efficacy. We explored the relationship between hTERT and cyclooxygenase 2 (COX2) and evaluated synergistic anti-cancer effects of targeting both hTERT and COX2.Methods:hTERT was depleted in gastric and cervical cancer cells using small interfering RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Consistently, Wu et al showed that BC cells with either −124C>T or −146C>T mutations acquired enhanced cellular motility [ 132 ]. In addition, TERT was further shown to protect cancer cells from apoptosis stimulated by various insults or stresses [ 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. Taken together, the TERT promoter mutation enhances high TERT expression, thereby contributing to aggressive phenotypes of cancer cells and poor patient outcomes via both telomere lengthening-dependent and independent mechanisms.…”
Section: Tert Promoter Mutations: Novel Prognostic Factors In Cancmentioning
confidence: 99%
“…Consistently, Wu et al showed that BC cells with either −124C>T or −146C>T mutations acquired enhanced cellular motility [ 132 ]. In addition, TERT was further shown to protect cancer cells from apoptosis stimulated by various insults or stresses [ 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. Taken together, the TERT promoter mutation enhances high TERT expression, thereby contributing to aggressive phenotypes of cancer cells and poor patient outcomes via both telomere lengthening-dependent and independent mechanisms.…”
Section: Tert Promoter Mutations: Novel Prognostic Factors In Cancmentioning
confidence: 99%
“…Although, in the present study, both agents markedly reduced telomerase activity in all seven cell lines, inhibition of SR was observed in only 4 (25%) out of 16 conditions. Telomerase inhibition results in stimulation of COX2 and mammalia target of rapamycin complex 1 and inhibition of autophagy (22,23). This may indicate that reduced telomerase activity may be necessary but not sufficient to inhibit SR capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This drives the prolonged expression of target genes critical for the maintenance of tumor survival and proliferation [53]. However, hTERT depletion alone did not affect cancer cell survival [54].…”
Section: Discussionmentioning
confidence: 99%